1998
DOI: 10.1016/s0272-6963(97)00037-5
|View full text |Cite
|
Sign up to set email alerts
|

An international comparison of environmental management in operations: the impact of manufacturing flexibility in the U.S. and Germany

Abstract: Pressures to improve environmental management in the U.S. and Germany are among the strongest in the world, demanding quick responsiveness from managers of manufacturing firms. However, even in these countries, the managerial implications of environmental regulation can vary dramatically. Our synthesis of related literatures indicates that manufacturing flexibility, by enabling efficient adaptation to change and uncertainty, can support environmental management. This paper empirically explores the linkage betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
60
0
2

Year Published

1999
1999
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(66 citation statements)
references
References 15 publications
4
60
0
2
Order By: Relevance
“…A number of dimensions define environmental management practices (Arag ! on-Correa, 1998; Klassen & Angell, 1998;Klassen & Whybark, 1999). Klassen and Angell (1998) found that manufacturing firms introduced such practices as a result of environmental legislation, as well as from a genuine desire to adopt them.…”
Section: Variables and Measurementsmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of dimensions define environmental management practices (Arag ! on-Correa, 1998; Klassen & Angell, 1998;Klassen & Whybark, 1999). Klassen and Angell (1998) found that manufacturing firms introduced such practices as a result of environmental legislation, as well as from a genuine desire to adopt them.…”
Section: Variables and Measurementsmentioning
confidence: 99%
“…on-Correa, 1998; Klassen & Angell, 1998;Klassen & Whybark, 1999). Klassen and Angell (1998) found that manufacturing firms introduced such practices as a result of environmental legislation, as well as from a genuine desire to adopt them. In a similar vein, Wolters, James, and Bouman (1997) distinguished between two dimensions of business environmental activities: environmental management and total performance.…”
Section: Variables and Measurementsmentioning
confidence: 99%
“…However, in the past several years, environmental forces such as consumer boycotts, dynamic preferences, new customer requirements, and global environmental conventions have affected basic business strategies as well as corporate core values (Berry & Rondinelli, 1998;Bhushan & MacKenzie, 1994; Klassen & Angell, 1998; Klassen & Whybark, 1999). Consequently, organizations are evolving from a pollution control strategy to a prevention strategy (Brockhoff, Chakrabarti & Kirchgeorg, 1999 To achieve this evolution, many companies seek to develop and deploy a formal Environmental Management System (EMS).…”
Section: Introductionmentioning
confidence: 99%
“…No intuito de atender à exigência crescente de consumidores ambientalmente responsáveis, preparar-se para o endurecimento da legislação ambiental (Klassen & Angell, 1998), evitar conflito com Organizações Não-Governamentais (ONGs) e aproveitar a possibilidade da diminuição de custos através de mecanismos de desenvolvimento limpo (MDL) (Salazar Filho, 2002), as organizações passaram a desenvolver, em suas estruturas, áreas específicas para atuar interna e externamente em melhorias de desempenho ambiental (Moura, 2008).…”
Section: Gestão Ambiental Empresarialunclassified